2015
DOI: 10.1007/s00468-015-1227-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive measurement of leaf area and dry biomass in Tectona grandis

Abstract: Leaf area and leaf dry biomass are key parameters linked to plant production and they are used in functional–structural plant models to simulate plant growth, but they are difficult to ascertain. Measuring leaf dimensions (length and width) to estimate them provides a non-destructive and rapid approach that can be used in the field. This was tested on teak (Tectona grandis) in Togo. Leaves were sampled to maximize variability in sizes along two categories of axes and at different ranks on the growth units. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
2
17
0
7
Order By: Relevance
“…We found that a power law model described the relation between Coffea leaf mass and the product of its length by width. The same model has been found for Tectona grandis (Tondjo et al 2015). As the measured leaves in this study were sampled at several node ranks of the leafy axis, and the leaves therefore had different ages, the observed trend might be explained by an increase in leaf thickness with leaf age (Niinemets 2001).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We found that a power law model described the relation between Coffea leaf mass and the product of its length by width. The same model has been found for Tectona grandis (Tondjo et al 2015). As the measured leaves in this study were sampled at several node ranks of the leafy axis, and the leaves therefore had different ages, the observed trend might be explained by an increase in leaf thickness with leaf age (Niinemets 2001).…”
Section: Discussionsupporting
confidence: 68%
“…We described an estimation of leaf area from simple non-destructive measurements in three Coffea species with a linear regression including the product of leaf length by width. As in teak, this linear relation resulted from leaf expansion due to intercalary meristem activity (Bell 1991;Tondjo et al 2015). The equations were similar between the axis categories of one species and between species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, sandy soil was considered as a rather infertile environment, especially for N. In addition, P sat , gs, and chlorophyll concentrations were also lower from April 2014 (Figures 6 and 8). The photosynthetic rate and chlorophyll concentration show positive correlations with the concentration of N [19,[43][44][45]66], and these decreases were related to decreased N in leaves. In terms of stomatal conductance, a leaf suffering from N deficiency can readily suffer from a decrease in leaf water potential [67].…”
Section: Discussionmentioning
confidence: 99%
“…We also measured length and width for all leaves of the teak seedlings. The leaf area of teak seedling was calculated from the equation of Tondjo et al [43], as follows:…”
Section: Measurement Of Teak Seedlingsmentioning
confidence: 99%